2014
DOI: 10.3109/14992027.2014.938370
|View full text |Cite
|
Sign up to set email alerts
|

The ICF core sets for hearing loss project: Functioning and disability from the patient perspective

Abstract: Objective: To explore areas of functioning, disability and environmental factors of adults with hearing loss (HL) by using the ICF classification as a tool to determine and document each element. Design: A qualitative study applying mainly focus-group methodology was applied). Conclusions: The present study illustrates the complexity and comprehensiveness of aspects involved in functioning and disability of adults with HL. The findings highlight the necessity of using a multidimensional tool, such as the ICF, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 40 publications
1
48
0
3
Order By: Relevance
“…For example, in functional impairment category, hearing problems and tinnitus were reported for PQ, whereas emotional problems were identified by the LEQ. Regarding environmental factors, previous research has identified a number of human-related environmental factors as relevant for adults with bilateral HL, reinforcing the results of the present study 9,10 . Furthermore use of an open-ended questionnaire allowed tapping into some of the nonauditory problems that these individuals may experience.…”
Section: Discussionsupporting
confidence: 88%
“…For example, in functional impairment category, hearing problems and tinnitus were reported for PQ, whereas emotional problems were identified by the LEQ. Regarding environmental factors, previous research has identified a number of human-related environmental factors as relevant for adults with bilateral HL, reinforcing the results of the present study 9,10 . Furthermore use of an open-ended questionnaire allowed tapping into some of the nonauditory problems that these individuals may experience.…”
Section: Discussionsupporting
confidence: 88%
“…M's findings are discussed using the ICF framework because it highlights the broad impact of hearing loss, auditory processing difficulties, aphasia, and other poststroke disabilities on people's lives. [5][6][7][8][9][10] EFFECTS OF STROKE ON COMMUNICATION AND AUDITORY PROCESSING Stroke continues to be a major cause of disability internationally despite evidence for declining rates of intracerebral hemorrhage in some populations. [11][12][13][14][15] As stroke is more common in older patients 16 ; hearing professionals are likely to encounter clients with hearing difficulties who have experienced a stroke.…”
Section: Abstract: Stroke Aphasia Auditory Processing Icf Hearingmentioning
confidence: 99%
“…The comprehensive and brief core sets for hearing loss, as described in Meyer et al (this issue), offer a standard for hearing health professionals to document patients' functioning and a system for policy makers and researchers to quantify profiles of health conditions. 24 To date, just one publication purposefully linked the brief core set for hearing loss to audiological assessment. 23 In this article, we will use the core sets for hearing loss to describe the functioning and disability of an older adult with hearing impairment and a significant other.…”
Section: Clinical Use Of the Icfmentioning
confidence: 99%